Convergence of Indonesia-South Korea Green Economy Strategy: A Case Study of Hyundai Motor Group's Investment in the EV Industry - Mulyaman, Darynaufal; Agustina, Dwi; Figo, Rudolf Davier; Sipahutar, Gabriel Alexander Mahameru; Rafsanjani, Abdullah Akbar (Journal of Strategic and Global Studies, 2025)
Hyundai Motor Group's investment in the electric vehicle (EV) industry in Indonesia reflects the convergence of green economy strategies between Indonesia and South Korea. The study aims to analyze the contribution of Hyundai investment in the development of the local EV ecosystem, including technology transfer, supporting infrastructure, and its impact on the bilateral relationship between the two countries. The research method used is a qualitative study with a case study approach. The results show that Hyundai Motor Group's investment supports Indonesia's green economy policy, despite challenges related to dependence on natural resources and infrastructure. This research contributes to academics and policymakers in understanding the role of foreign investment in the sustainable energy transition.